Effect of Intra Vitreal Injection of Bevacizumab on Intra-Ocular Pressure. - Sulman Jaffar, Ali Tayyab, Amena Masrur, Atif Majeed, (Journal of Rawalpindi Medical College, 2013)
Background To evaluate the effect of intra-vitreal injection of Bevacizumab on Intra-ocular pressure Methods: In this descriptive study sixty six patients who required intra-vitreal injection of Bevacizumab were enrolled. Patients with prior history of glaucoma, ocular hyper-tension, known allergy to Bevacizumab or who had prior injections of Bevacizumab were excluded from the study. Intra-ocular pressure was measured in the eye, using a Goldmann applanation tonometer, prior to the injection and for the purpose of this study seven days after the injection. The pre- and post- injection Intra-ocular pressure was entered into the database. Results: The mean age of the patient was 56.97 years (±13.805). The mean pre-injection intra-ocular pressure was 13.86 (±3.656) mmHg, while post-injection mean IOP was 15.43 (±5.498) mmHg. There was a statistically significant rise in intra-ocular pressure after injection of Bevacizumab (p=0.01). Conclusion: Intra-vitreal injection of Bevacizumab is associated with a statistically significant rise in intra-ocular pressure.